2017
DOI: 10.1002/mame.201700402
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Rheological Behavior of Hybrid Cross‐Linked Polyacrylamide/Cationic Micelle Hydrogels

Abstract: with an ionic cross-linking alginate-Ca 2+ network, which exhibit highly stretchable property of beyond 20 times their initial length and remarkable fracture energy of nearly 9 kJ m −2 . [15] Chen et al. engineered hybrid Agar/PAM hydrogels, which exhibited high stiffness of 313 kPa and high toughness of 1089 J m −2 . [16] They also fabricated fully physical cross-linking DN hydrogels combing Agar with hydrophobic associated PAM, which showed rapid selfrecovery and self-healing properties at room temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
(27 reference statements)
5
33
0
Order By: Relevance
“…Moreover, the critical strain value of the HPAAm/alginate‐Ca 2+ DN hydrogel was smaller than the other two hydrogels. This indicated that the crosslinking density of the HPAAm/alginate‐Ca 2+ DN hydrogel was higher than the other two hydrogels, owing to the critical strain decreasing with the increasing of crosslink density for the network . These results are in accordance with the results obtained from the stress–strain curves.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the critical strain value of the HPAAm/alginate‐Ca 2+ DN hydrogel was smaller than the other two hydrogels. This indicated that the crosslinking density of the HPAAm/alginate‐Ca 2+ DN hydrogel was higher than the other two hydrogels, owing to the critical strain decreasing with the increasing of crosslink density for the network . These results are in accordance with the results obtained from the stress–strain curves.…”
Section: Resultssupporting
confidence: 87%
“…This indicated that the crosslinking density of the HPAAm/alginate-Ca 2+ DN hydrogel was higher than the other two hydrogels, owing to the critical strain decreasing with the increasing of crosslink density for the network. [33,34] These results are in accordance with the results obtained from the stress-strain curves. Figure 9b showed the frequency sweep data of the HPAAm hydrogel, HPAAm/alginate hydrogel, and HPAAm/alginate-Ca 2+ DN hydrogel.…”
Section: Dynamic Rheology Behaviorsupporting
confidence: 90%
“…Rheological properties are very important criteria for determining the three‐dimensional structure of the crosslinked polymer molecular chains 42 . Figure 3(e,f) showed the changes of storage and loss modulus of hydrogels with different contents of OMWCNTs in the frequency range of 0.1–100 rad/s, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Rheological properties are very important criteria for determining the three-dimensional structure of the crosslinked polymer molecular chains. 42 Figure 3(e,f) showed the changes of storage and loss modulus of hydrogels with different contents of OMWCNTs in the frequency range of 0.1-100 rad/s, respectively. In the test region, the storage modulus (G 0 ) of all these hydrogels with or without OMWCNTs were much higher than their loss modulus(G 00 ), which implied the good elastic behavior of the composite hydrogels.…”
Section: Mechanical Properties Of Hydrogelsmentioning
confidence: 99%
“…57 The AAm control hydrogel presented a less pronounced strain overshoot, which has been observed by others. 58,59 This behaviour, observed in AAmbased hydrogels, may be related to the presence of an additional structure associated by hydrogen bonding that imposes some resistance to deformation. 57 In all other gels a strain thinning behaviour is observed, in which as strain is increased polymer chains disentangle to align with the direction of flow.…”
Section: Polymer Chemistry Papermentioning
confidence: 97%